Study on the Optimal Production Pressure of Different Types of Natural Gas Hydrate Based on Formation Stability. (23rd October 2020) - Sun, Ting; Chen, Yuan; Yang, Jin; Li, Qingping; Pang, Weixin
Abstract : Natural gas hydrate is an ice-like crystal formed by methane and water, which is a new type of strategic energy with huge reserves. The exploitation of deep-sea hydrate will cause a large amount of decomposition of hydrate, which will decrease the sediment strength. In this paper, production models of different types of hydrate reservoirs under different BHP (bottom hole pressure) were established. Then, sensitivity analysis was conducted to determine parameters which have the most significant influence on formation subsidence. After that, hydrate formation failure was discussed using two different criteria: formation subsidence and stress-strain curve. Then, critical production pressure was determined. Through comparison, it was found that the criterion of formation subsidence is more suitable. Finally, based on this criterion, the optimal production pressure of different types of hydrate reservoir was determined. The work of this paper will provide a certain reference value for the efficient and safe production of hydrate in the future.